One-pot Synthesis and Antibacteial Study of New Cyclohexenone Derivatives Catalyzed by Tetramethylammonium Hydroxide. (26th May 2020) - Mojtabaei, Fereshteh; Mokhtary, Masoud
GRAPHICAL ABSTRACT: ABSTRACT: The direct three-component reaction of 2-acetylnaphthalene, benzaldehydes, and acetoacetanilide to produce a novel series of cyclohexenone derivatives has been carried out over tetramethylammonium hydroxide pentahydrate in ethanol at 70°C. One-pot reaction, high efficiency, short reaction time, and easy purification of products by simple recrystallization are some of the considerable advantages of this procedure. The produced cyclohexenone derivatives were screened for their antibacterial activity against Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa . The results showed that the cyclohexenones 4g, 4i, and 4j had good antibacterial activity toward Escherichia coli and the cyclohexenones 4j and 4k had good antibacterial activity against Staphylococcus aureus.